2020
DOI: 10.1080/21645515.2020.1839292
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of the nine-valent human papillomavirus vaccine in Scandinavian women: interim analysis after 8 years of follow-up

Abstract: A long-term follow-up (LTFU) of the nine-valent human papillomavirus (9vHPV) vaccine efficacy study in young women aged 16–26 years was initiated to evaluate if vaccine effectiveness for up to 14 years post-vaccination will remain above 90%. Vaccine effectiveness is measured as percent reduction in the incidence of HPV16/18/31/33/45/52/58-related high-grade cervical dysplasia in the LTFU cohort relative to expected incidence in a similar unvaccinated cohort. We report an interim analysis 8 years post-vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…Besides, the immunogenicity results of a long-term study on quadrivalent vaccine have indicated sustained antibody responses against genotypes 6, 11, 16 and 18 up to fourteen years after immunization [19]. These conclusions are in line with the excellent results of an interim analysis (follow-up at 8 years) carried out on Scandinavian women vaccinated with the nonavalent vaccine; this analysis has confirmed the absence of high-grade lesions caused by the genotypes included in the vaccine in immunized women and the persistence over time of efficacy [19,20].…”
Section: Vaccines Available In Europe and Italy Primary Target Schedule And Differences Between Italian Regionssupporting
confidence: 67%
“…Besides, the immunogenicity results of a long-term study on quadrivalent vaccine have indicated sustained antibody responses against genotypes 6, 11, 16 and 18 up to fourteen years after immunization [19]. These conclusions are in line with the excellent results of an interim analysis (follow-up at 8 years) carried out on Scandinavian women vaccinated with the nonavalent vaccine; this analysis has confirmed the absence of high-grade lesions caused by the genotypes included in the vaccine in immunized women and the persistence over time of efficacy [19,20].…”
Section: Vaccines Available In Europe and Italy Primary Target Schedule And Differences Between Italian Regionssupporting
confidence: 67%
“…The observation periods for the 9-valent vaccine was 5 years in a Latin American study [52], 6 years in the extension V503-001 [53], 8 years in a Scandinavian study [55] and 8 years in the LTFU extension study [54].…”
Section: -Valent Vaccine 431 Young Womenmentioning
confidence: 99%
“…Kürzlich ist der ultimative Beweis geliefert worden, dass durch die HPV-Impfung nicht nur Infektionen und Krebsvorstufen, sondern auch invasive Karzinome verhindert werden [10,11]. Dies ist ein Meilenstein und global ist das Zervixkarzinom nach wie vor eines der häufigsten Karzinome.…”
Section: Diskussionunclassified